Victor Grant Collection, Album 5, Photograph 277 Frank D. and William H. Lambert
On back of photgraph: " Left to right: Frank D. Lambert, William H. Lambert. Maywood, California, December 1926."
Designation 5.277 in listing stands for Album 5, Photograph 277.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Lambert, Frank D; Lambert, William H; Lambert family. -- New Mexico; Genealogy - Photographic collection